2020
DOI: 10.3390/ijerph17228533
|View full text |Cite
|
Sign up to set email alerts
|

Is Irritable Bowel Syndrome Considered in Clinical Trials on Physical Therapy Applied to Patients with Temporo-Mandibular Disorders? A Scoping Review

Abstract: The aim of the current scoping review was to identify if the presence of irritable bowel syndrome was included as eligibility criteria of participants included in clinical trials investigating the effects of physical therapy in individuals with temporomandibular pain disorders (TMDs). A systematic electronic literature search in the Web of Science database was conducted. Scientifically relevant, randomized clinical trials (those cited in other studies at least 5 times, or clinical trials published in high-impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…If medical comorbidities are ignored in the selection criteria of clinical trials, this may limit the potential benefits of physical therapy, which mainly targets musculoskeletal symptomatology. In fact, it has already been identified that the comorbid relationship of IBS with temporomandibular disorders [19,20] is underreported when designing clinical trials evaluating the effectiveness of physical therapy [21]. It is, therefore, reasonable to consider that the relationship of FM with IBS could also influence clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…If medical comorbidities are ignored in the selection criteria of clinical trials, this may limit the potential benefits of physical therapy, which mainly targets musculoskeletal symptomatology. In fact, it has already been identified that the comorbid relationship of IBS with temporomandibular disorders [19,20] is underreported when designing clinical trials evaluating the effectiveness of physical therapy [21]. It is, therefore, reasonable to consider that the relationship of FM with IBS could also influence clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%